Research on industrial control system intrusion detection method based on simulation modelling - Yi-wei GAO; Rui-kang ZHOU; Ying-xu LAI; Ke-feng FAN; Xiang-zhen YAO; Lin LI (Tongxin xuebao)
At present,intrusion detection system over fieldbus network layer was a basic protection method in industrial control system.However,it has some weakness,such as poor generality,high false-positive rate,and unable to detect unknown anomaly.An industrial control system intrusion detection method based on fieldbus network equipment simulation was proposed.The method prevented control program from being tampered or destroyed based on controller simulation modelling.Controlled object simulation modelling was designed for ensuring that the system input was credible.Thus the intrusion detection of industrial control network was realized.At last,the results indicate that the proposed intrusion detecting method is available.